Commissioning of beam shaper applicator for conformal intraoperative electron radiotherapy. (May 2017) - Heidarloo, Nematollah; Baghani, Hamid Reza; Aghamiri, Seyed Mahmoud Reza; Mahdavi, Seyed Rabi; Akbari, Mohammad Esmail
Abstract: Beam shaper is a newly designed device for beam shaping in IOERT. The aim of this study is evaluating the performance of this device for conformal IOERT and preparing it for clinical applications. Dosimetric characteristics for different combinations of energy/field size were determined by ionometric dosimetry, film dosimetry and Monte Carlo simulation. Desirable dosimetric characteristics of beam shaper make it a useful tool for conformal IOERT. Usability of Monte Carlo simulation in any clinical setup of beam shaper was demonstrated. Highlights: Beam shaper applicator is a newly designed device for IOERT. Dosimetric characteristics of beam shaper were obtained and analyzed. Introduced applicator can be considered as a useful tool for conformal IOERT. Application of Gafchromic film dosimetry in commissioning of beam shaper was demonstrated. Application of Monte Carlo simulation in any clinical setup of beam shaper was proven.